CHEMICAL SCREENING OF CHIRATA (SWERTIA CHIRAYITA KARST COLLECTIONS FROM HIMACHAL PREDESH FOR BITTER CONTENT VARIABILITY - Dutt, Bhupeder (Medknow Publications & Media Pvt Ltd, 1999)
The investigations were carried out on collations of the herb made from natural habitats with altitudes ranging from 1500 m to 2700m. the material was subjected to chemical screening which revealed a great deal of variation ranging from 0.75 percent to 1.14 per cent wit respect to bitter content which is a pharmaceutically important component of this plant. Besides this observations were also recorded on the effect of root length and root thickness on the yield of bitter principles, observations recorded on soil parameters did not reveal any significant effect on the bitter content production except soil pH.